Mathematical and computational modeling for the determination of optical parameters of breast cancer cell. (2nd October 2021) - Hossain, Shadeeb; Hossain, Shamera
ABSTRACT: This study enumerates the quantitative measurement of optical parameters used in several diagnostic procedures for malignant tissue. Optical diagnosis is proposed due to its non-invasive and non-destructive nature. This paper recapitulates Fresnel equation (polarization independent) to determine the characteristic critical angle of malignant tissue. The critical angle of malignant tissue is lower than healthier tissue and is therefore an optical parameter of interest for lesion tissue diagnosis. Similarly, a quantitative analysis is derived to commensurate refractive index and absorption and reflective property of tissue and its nuance with healthier counterparts. The second dichotomy of the research concentrates on comparing and validating the mathematical analysis with COMSOL Multiphysics® 5.2 simulation. The magnitude of malignant tissue reflectance is obtained across a range of incident angle ranging from 0° to 90°. The simulation results satiate the quantitative analysis with only 1.3% deviation. This quantitative result provides prospect of collaborating bio-electromagnetism results with Artificial Intelligence technology for active disease progression diagnosis utilizing minimum invasive diagnostic procedure.